Spatial Variability of P/Zn Ratios on Calcareous Soil Under the Wheat Plants (Triticum aestivum) - Karaman, M.Rustu; Sahin, Sezer; Coban, Serpil; Sert, Tuba (Asian Journal of Chemistry, 2010)
One of the main reasons of available Zn deficiency of the soils is excessive application of phosphorus (P) fertilizers. However, the ratio of P/Zn in the field soil is essential for optimal Zn use by the crops; there is little information concerning this ratio depending on varied soil and plant conditions. In this study, topsoil (0-20 cm), subsoil (20-40 cm) and plant samples were collected from the plots based on a 25 x 25 m grid under the wheat plants. The coefficient of variance (C.V.), kurtosis and skewness values revealed that a great spatial variability occurred in available P, Zn and P/Zn ratio for topsoil. Contour map of site-specific Zn contents indicated that the experimental topsoil had mainly sufficient amounts of available Zn (average 0.85 mg kg-1), whereas, three dimensional map of Zn concentrations of wheat plants indicated that about 98% of the plants on these soils had a low level of Zn (11-20 mg kg-1). Significant correlation, r = 0.48 and P < 0.0 I, was also found between the sitespecific P/Zn ratios in the topsoils and P/Zn ratios in the wheat plants. The findings clearly show that the site-specific P/Zn ratio in the field soil was an important factor for maximum Zn utilization by the wheat plants. Hence, fertilization programme based on site specific P and Zn demands of the wheats will increase Zn use efficiency of the plants with proper P/Zn ratios. Contour maps based on proper site-specific samplings will provide more accurate information for balancing P/Zn ratios.